Sustainability, Innovation, and Entrepreneurship - Larson, Andrea (Open textbook library., 2011)
This book is suited for the Entrepreneurship or Innovation course with an emphasis on Sustainability or for a course devoted entirely to Sustainability. What are the trends and forces underlying the changing character of the business-environment relationship? How they are creating significant entrepreneurial opportunities for individuals and companies? Around the world, the movement toward ”sustainable development“ has caused many firms to adopt policies and practices that reflect what is sometimes called a ”sustainable business“ or ”triple bottom line“ approach. ”Triple bottom line“ refers to the demonstration of strong performance across economic, social, and environmental indicators. Those measures serve as indicators of fiduciary responsibility to a growing set of concerned investors and therefore can help ensure access to capital. They also enable innovators to lower costs, create strategic differentiation, reduce risk, and position themselves for competitive advantage over rivals less attuned to trends. The deep roots of sustainability thinking are now evident in widespread and increasingly visible activities worldwide, and Sustainability, Innovation, and Entrepreneurship explores this evolution; its necessity, its implications and its progression.